Evaluation of Nurses Practices about Pain Related Management for Children with Burns Injuries - Najat Kaittan Lafta, Khatam M.Al-Mosawi, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Burn injury occurs to the skin or other organic tissue primarily result in from exposure or direct contact to any type of chemical, thermal, electrical, or radiation. Material and Method: The study selected quantitative research " a pre-experimental design" to carry out at Specialized Burn Center at Al-Fayhaa Teaching Hospital in Basra City to evaluate the practice of nurses about pain-related management for children with burns Injuries, the study started from (3th of December 2021 to 20th of March 2022). The Sample of the Study choosing the study sample, the total population was taken into consideration and the excluded sample was determined. A non-probability (Purposive) sample is used to obtain accurate data and are presentative sample was selected for the current study. Results: The results showed that the nurses sample in the study, that 40.0% (12) of the sample at age (21-30) years with mean (1.90) and standard deviation (0.845), the sample gender was equal in number between male and female with mean (1.50) and standard deviation (0.509), 63.3% (19) of them was nursing institute of educational level with mean (1.63) and standard deviation (0.490), 40.0% (12) of the sample at (1-5) years of experience in nursing with mean (2.27) and standard deviation (1.258), Conclusion: The study concluded that the nurses’ practices about pain related management for children with burns injuries was acceptance.